Absence of 18F‐fluorodeoxyglucose uptake using Positron Emission Tomography/Computed Tomography in Madelung's disease: A case report. Issue 3 (27th February 2019) - Moonen, Michiel P.B.; Nascimento, Emmani B.M.; van Kroonenburgh, Marinus J.P.G.; Brandjes, Dees; van Marken Lichtenbelt, Wouter D.
Abstract : Madelung's disease is characterized by the manifestation of multiple ectopic lipomas, usually found in the cervical‐thoracic region, however, clinical manifestation may vary among patients. It has been postulated that lipomas associated with Madelung's disease are linked to brown adipose tissue (BAT) due to the presence of uncoupling protein 1 (UCP1). Therefore, we here investigated whether BAT activity is present in a patient with Madelung's disease. 18 F‐fluorodeoxyglucose ( 18 F‐FDG) uptake using PET/CT after a cooling procedure was measured together with body temperature and energy expenditure. Finally, adipose tissue biopsies were taken from the lipomas for gene expression analysis and histology. 18 F‐FDG uptake was not detected after the cooling procedure in the lipomas. Furthermore, adipose tissue biopsies derived from the lipomas did not express UCP1. We thus conclude that cold‐stimulated BAT activity was not detected in lipomas associated with Madelung's disease. Additional research in other patients is needed to unravel the role of dysfunctional BAT in Madelung's disease.